INTERACTIONAL METADISCOURSE IN ACADEMIC PRESENTATION BY STUDENTS OF FOURTH SEMESTER OF UNIVERSITAS QOMARUDDIN - Eva Nur Mazidah; Fauziyatun Ni'mah; Maslakhatul Ainiyah (English Language Teaching Department (Prodi Pendidikan Bahasa Inggris), 2019)
Doing academic presentation is a requirement in Speaking class for the fourth semester students in English Language and Teaching Program. Students not only focus on the materials for the presentation, but also prepare their performance in front of the audience. As the goal of presentation is to share information to their classmates, they are demanded to present effectively so their audience understand what they would like inform in the presentation. 19 presenters performed, and metadiscourse markers of their spoken words were analyzed. It is found that the highest usage is in engagement markers (46.54%), hedges (21.24%), self-mentions (19.33%), boosters (11.93%), and attitude markers (0.95). The results show that all speakers utilize metadiscourse markers (using Hyland’s classification) and each speaker has their style in utilizing these markers in organizing their ideas.